Identification of Potential Consumer Segments of Smoked Tuna (Thunnus spp.) through E-commerce: Identification of Potential Consumer Segments of Smoked Tuna (Thunnus spp.) through E-commerce - Ma'rifat, Tian Nur; Suprihatin, Febriyani Eka; Waluyo, Eko; Rahmawan, Arief (Universitas Darussalam Gontor, 2025)
This study explores consumer segmentation for smoked seafood in Indonesian e-commerce, aiming to identify distinct buyer groups and their preferences. The problem lies in the limited understanding of market segmentation and the absence of smoked tuna trade through e-commerce platforms in Indonesia, despite the country's significant tuna production capacity. The research categorizes different consumer segments by analyzing key factors shaping their purchasing decisions. Data were collected from 246 respondents who had purchased smoked tuna from Prigi Beach and had prior e-commerce experience. K-means clustering analysis was applied to classify respondents into two clusters based on their demographic characteristics, behaviors, and perceptions. The study observed three key behavioral variables: Perceived Social Norm (PSN), Perceived Relative Advantage (PRA), and Perceived Health Benefit (B). Cluster 1, comprising 53% of respondents, is characterized by younger, health-conscious individuals, predominantly female, with a higher frequency of purchasing through e-commerce. They perceive e-commerce as a faster, more cost effective option and show stronger intentions to buy smoked seafood due to its nutritional value, distinctive taste, halal certification, affordability, and convenience. In contrast, Cluster 2, accounting for 47% of respondents, has a more varied demographic and lower frequency of online purchases. The findings suggest that Cluster 1 presents a more promising target for producers. By focusing on this segment's preferences and leveraging digital platforms, businesses can optimize their marketing strategies, enhance consumer engagement, and expand market reach. These results highlight the potential of e-commerce as a transformative platform for the seafood industry, offering insights into consumer segmentation and strategic opportunities for market growth. Keywords: cluster; consumers; market potential; online platforms